An Investment Strategy Based on Leverage: Evidence from BSE 500. (December 2015) - D'Mello, Lorraine; Sivaprasad, Sheeja
This article examines the value relevance of leverage to equity investors. We construct a short-term investment strategy based on leverage of Indian firms over a 10-year period. We examine the ability of leverage to predict stock returns by analysing the cumulative abnormal returns (ARs) for a holding period of 1 year. We show that returns increase in leverage. Robustness tests are carried out to examine the returns in excess of those attainable using firm characteristics, such as, size, price to book, price–earnings (P/E) and dividend yield (DY). Our findings show that portfolios based on size and leverage can yield an excess return of up to 23 per cent. JEL Classification: G1, G3, G32